A simplified model for alternate load path assessment in RC structures. (15th September 2018) - Lim, Namyo Salim; Tan, K.H.; Lee, C.K.
Highlights: A simple analytical model to predict the resistance of RC frame-slabs is proposed. The proposed model is verified with experimental results of RC frames/frame-slabs. The proposed model is applied to 2D frames and unsymmetrical double-span beams. The proposed model is simple and can provide reasonably conservative predictions. Abstract: To assess the robustness of reinforced concrete structures under progressive collapses, alternate load path method by introducing a single column removal has been widely adopted by structural engineers. Numerical analyses of structures under several possibilities of single column removal may be time consuming, especially when non-linear finite element analyses are employed which require high computational costs and modelling skills. Towards this end, a simplified analytical model is proposed in this paper to facilitate engineers in predicting resistance of the affected substructure (frames or frame-slabs above the removed column), and allow them to perform a quick check on the adequacy of progress collapse resistance of the structure to stop or prevent the damage propagation to the remaining structure. The proposed model considers development of different bridging mechanisms in RC structures under a concentrated loading above the removed column, including compressive arch action, catenary action, and tensile membrane action. In addition to validation against test results, applications of the proposed analytical model to predict the bridging capacities of a 2-D two-storey frame and unsymmetrical double-span beams are also presented.